Perception on health and exercise among indonesian older adults: a sequential exploratory study in javanese rural communities - Agam Akhmad Syaukani; Gatot Jariono; Nugroho Susanto; Hendra Setyawan (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This study aims to investigate the perceptions of health and exercise among older adults in rural Javanese communities in Indonesia. Through a sequential exploratory approach, the research uncovers diverse levels of knowledge regarding health and exercise among the rural population. There are 40 older adults from three different regency in Central Java Province participated in filling out the Global Physical Activity Questionnaire (GPAQ). Further qualitative analysis used 25 samples out of 40 through convenient method. Semi-structured interview is conducted to confirm results of questionnaire and explore their perception on health and exercise. Despite variations, a predominant belief emerges among participants regarding the significant health benefits associated with exercise. Analysis reveals that a considerable majority (87.5%) of participants meet the World Health Organization's recommended standards of >600 METs/week, primarily through work-related physical activities. However, there remains a notable disparity in the prevalence of physical activity during leisure time, particularly in engaging in sport-related physical activities. The accumulated METs score dominantly comes from work and travel-related activities. Qualitative study reveals that there are still few initiatives among older adults to adopt a healthy living through sports and exercise. Some believe that sports were never part of their culture. To address these findings, we urge for strategic interventions from stakeholders to enhance awareness among rural older adults about the importance of sports and exercise to enhance the overall well-being. This entails the implementation of health education programs and the facilitation of collective exercise activities at the village level.